Analisa Studi Kelayakan Bisnis Gula Alternatif Stevia di PT. Mitra Kerinci - Zulhamdi Zulhamdi (Jurnal Ilmu Manajemen, 2020)
The analysis of Stevia feasibility study at PT. Mitra Kerinci as the alternative product of sugar business aims to analyze and study the level of Stevias feasibility as alternative product of sugar business as well as what marketing strategies will be used to develop Stevia as sugar business alternative. The analysis of this feasibility study was assessed using feasibility study aspects as follows; market and marketing aspect, production and technology aspect, management and human resource aspect, legal aspect, social and environment aspect, and also financial and economic aspect. From the calculation of the five methods it can be shown that the plan to develop Stevia as sugar business alternative at PT. Mitra Kerinci is acceptable and feasible to run. The strategy that can be applied is by supporting the policies of aggressive growth. The marketing pattern that can be developed must be a vigorous promotion and must be able to influence consumers to replace sugar into Stevia sugar